Method Used In Teaching Speaking To The Second Year Students Of SMP N 1 Karangdowo, Klaten In Academic Year 2012/2013 - Prastiwi, Nira, Prof. Dr. Endang Fauziati, M.Hum., Nur Hidayat, S.Pd (2013)
The study investigates the method used in teaching speaking to the second year students of SMP N 1 Karangdowo, Klaten in academic year 2012/2013. The objective of the study is to describe and to know the approach, the design and the procedure used in teaching speaking. Besides that, to know the strength and weakness of the method used in teaching speaking to the second year students of SMP N 1 Karangdowo, Klaten in academic year 2012/2013. The type of the study is descriptive qualitative especially ethnography. The subject of the study is English teacher and the second year students of SMP N 1 Karangdowo, Klaten. The object of the study focuses on the method used in teaching speaking especially in the first semester. In this research the data are derived from event, informant, and document. There are three technique of collecting data, namely: observation, interview, and document analysis. The result of the study shows that the method used by the teacher in teaching speaking divided into: 1) the approaches used by the teacher in teaching speaking are constructivism and humanism theories. 2) the design, include a) learning objectives of teaching speaking are to make the students speak well, to make the students create the dialog, to increase the ability of students' speaking, to enlarge the students' vocabulary. b) the syllabus model used by the teacher is text-based syllabus. c) the teacher has complete role as manager, facilitator, instructor, motivator, and evaluator. d) the students have role as subject in teaching speaking. e) evaluation used by the teacher is periodic test beside the mid and final tests. f) the material taken from the book, internet, while the media used by the teacher are whiteboard and LCD. 3) the procedure, the teacher divided into three steps, namely: pre-activity, main-activity, and post-activity in which the activity includes some techniques, namely: discussion and problem solving techniques. 4) strength and weakness, a) the strengths are role of the teacher in teach their student make effective and meaningful, the approach makes the students create their thinking ability, the material has many picture so help the students to understand the material. b) the weaknesses are the media is not used by the teacher maximally, the target language is used rarely so make the students less understand in English